DISCIPLINE AND MOTIVATION ANALYSIS OF EMPLOYEE PERFORMANCE IN PROPERTY COMPANIES IN BATAM CITY - Wasiman Wasiman; Yvonne Wangdra (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This research is motivated by the condition of property during the Covid-19 period where several sectors experienced the impact of the pandemic, one of which was property. The purpose of this study was to determine the effect of discipline and motivation on employee performance at a property company in Batam City. The method used in this study was to conduct a survey and distribute questionnaires to five large property companies in Batam City which were used as samples in the study. The number of samples used were 115 samples. The results of the validity test found that all the independent variables or the x variable, the discipline variable, work stress and motivation, and the y variable, namely performance, were all valid with a value above 0.6. The results of the reliability test found that all research variables were reliable. From the results of the study concluded that discipline, work stress and motivation on employee performance at property companies in Batam City. The results of the Q square test show that the independent variable can explain the dependent variable by 75%, which means that the variables of discipline, work stress and motivation can affect the employee performance variable by 75% while the remaining 25% is influenced by other variables outside the research variable. Keywords: discipline and Motivation, Employee performance